Generation of emotional inferences during the reading of narratives: using the Landscape model to simulate comprehension - Molinari Marotto, Carlos (2011)
This study investigated the generation of emotional inferences during the reading and recall of narrative texts. Experiment 1 compared the fit of two simulations of text comprehension to the recall data. One simulation examined causal and referential inferences, while the other examined causal, referential and emotional inferences. We found that the simulation that involved emotional inferences provided a better fit to the human data than the other simulation. Experiment 2 tested whether emotional inferences are generated online by recording lexical decision times at pre-inference and inference locations. Lexical decision times were faster at the inference than the pre-inference locations. These findings suggest that emotional inferences play a role in the understanding of natural texts, and that they require the reader to establish connections between text segments.ment 1 compared the fit of two simulations of text comprehension to the recall data. One simulation examined causal and referential inferences, while the other examined causal, referential and emotional inferences. We found that the simulation that involved emotional inferences provided a better fit to the human data than the other simulation. Experiment 2 tested whether emotional inferences are generated online by recording lexical decision times at pre-inference and inference locations. Lexical decision times were faster at the inference than the pre-inference locations. These findings suggest that emotional inferences play a role in the understanding of natural texts, and that they require the reader to establish connections between text segments.